2017
DOI: 10.1364/oe.25.012722
|View full text |Cite
|
Sign up to set email alerts
|

Few-mode optical fiber based simultaneously distributed curvature and temperature sensing

Abstract: The few-mode fiber (FMF) based Brillouin sensing operated in quasi-single mode (QSM) has been reported to achieve the distributed curvature measurement by monitoring the bend-induced strain variation. However, its practicality is limited by the inherent temperature-strain cross-sensitivity of Brillouin sensors. Here we proposed and experimentally demonstrated an approach for simultaneously distributed curvature and temperature sensing, which exploits a hybrid QSM operated Raman-Brillouin system in FMFs. Thanks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Since the first sensing demonstration with an SMF (BFS ~ 1.6 MHz for a 1.5 m of SMF winded around a rod of 25 mm diameter [52]), different optical fibers have been investigated. Among them, a few-mode fiber was used to improve the sensitivity (~5 time for a radius curvature of 0.8 cm) and to extend the range of curvature measurements (radius curvature from 0.7 cm to 3.4 cm) [53]. MCF was successfully used for demonstrating −1…”
Section: Distributed Sensing Of Other Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first sensing demonstration with an SMF (BFS ~ 1.6 MHz for a 1.5 m of SMF winded around a rod of 25 mm diameter [52]), different optical fibers have been investigated. Among them, a few-mode fiber was used to improve the sensitivity (~5 time for a radius curvature of 0.8 cm) and to extend the range of curvature measurements (radius curvature from 0.7 cm to 3.4 cm) [53]. MCF was successfully used for demonstrating −1…”
Section: Distributed Sensing Of Other Parametersmentioning
confidence: 99%
“…Since the first sensing demonstration with an SMF (BFS ~1.6 MHz for a 1.5 m of SMF winded around a rod of 25 mm diameter [52]), different optical fibers have been investigated. Among them, a few-mode fiber was used to improve the sensitivity (~5 time for a radius curvature of 0.8 cm) and to extend the range of curvature measurements (radius curvature from 0.7 cm to 3.4 cm) [53]. MCF was successfully used for demonstrating curvature radius and orientation measurements (with a BFS sensitivity of 2.06 MHz/m −1 ) by correlating the difference of BFS between the central core and outer six cores, paving the way to full 3D shape determination using an optical fiber [44].…”
Section: Distributed Sensing Of Other Parametersmentioning
confidence: 99%
“…For example, the temperature resolution along the fiber should be provided. Wu et al reported utilizing a QSM-operated FMF to design a novel Raman-Brillouin system for simultaneous distributed curvature and temperature sensing [55]. By adding a Raman filter to a conventional BOTDA setup, the authors separated the Raman and Brillouin signals, in the wavelength-domain.…”
Section: Fmf As a Compromise Between Standard Smf And Mmfmentioning
confidence: 99%
“…Very nice theoretical analyses of such interactions can be found in [129,130]. Xu et al [62,131] provided an analysis involving modes possessing orbital angular momentum, while Wu et al [132] described a hybrid Raman-Brillouin system in a few-mode fiber.…”
Section: Fiber Configurationsmentioning
confidence: 99%